Comprehensive Geriatric Assessment in Frail Older People: Thoughts on Application - WU Minjie, WU Shenhui, YAN Yuru (Zhongguo quanke yixue, 2023)
As China enters an ageing society, the number of elderly people is rising sharply, resulting in a continuous increase in the cost and burden of caring for the elderly. Frailty is an important cause of loss of self-care ability and elderly care problems in elderly people, which means that frailty is associated with a decline not only in physiological functions, but in multiple areas as well, such as mental ability and socioeconomic functioning, and is considered an important geriatric syndrome that affects the quality of life of the elderly. Comprehensive Geriatric Assessment (CGA) is a multi-dimensional and multi-disciplinary assessment process or model specifically for elderly patients. As a core tool in geriatric medicine, it uses a multi-dimensional and multi-disciplinary approach to assess the physical condition, functional status, mental health and social environment status of the elderly, and accordingly a treatment plan is developed to maintain and improve the functional status of the elderly and enhance their quality of life to the most extent. However, the use of CGA is not entirely consistent in China and abroad. This paper reviews the existing studies on frailty in the elderly, analyses the advantages and shortcomings of CGA used in frail elderly patients, and finds that interventions for frail patients at home and abroad have been valued increasingly. The development of domestic interventional studies on frailty is still in the initial stage, and most of these studies use a design of a randomized controlled trial with a sample of chronic disease inpatients. In contrast, such studies have been widely carried out abroad, in which CGA has been applied to the management of cancer patients and patients in the perioperative period besides chronic disease patients and frail community-dwelling older people. The frailty status in the elderly can be scientifically and comprehensively assessed by the CGA, and based on which targeted interventions can be implemented to prevent or delay the development of frailty, but it is generally time-consuming, and there are many difficulties in the management of the assessment recipients. In the future, it is necessary to advance the clinical application of CGA, or develop a more rapid, comprehensive and authoritative tool based on CGA for frailty assessment in the elderly, so as to provide comprehensive and personalized medical services and health guidance for frail elderly population through standardised assessment.